2019
DOI: 10.17556/erziefd.443298
|View full text |Cite
|
Sign up to set email alerts
|

Program Değerlendirme Doktora Tezlerine Ait İçerik Çözümlemesi (1996-2017)

Abstract: The aim of this research is to analyze the curriculum evaluation PhD dissertations in Turkey according to different variables and present the current situation. The Research is important in terms of helping to identify tendencies in this area and to monitor progress through setting out the current situation in the area of curriculum evaluation. In this research, PhD dissertations on curriculum evaluation which were written in Curriculum and Instruction Departments in universities in Turkey were examined by doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…In parallel with this, the theses on curriculum evaluation, included in the research, were written in the institutes of educational sciences (n = 303) and social sciences (n = 242). Also, in the studies carried out for the postgraduate theses completed in Curriculum and Instruction (CI), it was found that the universities such as Abant İzzet Baysal, Anadolu, Ankara, Atatürk, Fırat, Gazi, Hacettepe, and METU produced more theses in that field in the last fifteen years (Aslan & Sağlam, 2017;Kozikoğlu & Senemoğlu, 2016;Özüdoğru, 2018;Yetkiner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In parallel with this, the theses on curriculum evaluation, included in the research, were written in the institutes of educational sciences (n = 303) and social sciences (n = 242). Also, in the studies carried out for the postgraduate theses completed in Curriculum and Instruction (CI), it was found that the universities such as Abant İzzet Baysal, Anadolu, Ankara, Atatürk, Fırat, Gazi, Hacettepe, and METU produced more theses in that field in the last fifteen years (Aslan & Sağlam, 2017;Kozikoğlu & Senemoğlu, 2016;Özüdoğru, 2018;Yetkiner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This finding shows that the mixed method started to be selected for the theses on curriculum evaluation. When the postgraduate theses in the fields of CI and educational sciences were examined, it was found that quantitative methods were mainly preferred in general; there was a significant increase in the use of mixed methods especially after 2000, and qualitative methods were relatively less preferred (Eskici & Çayak, 2017;Gökmenoğlu, 2014;Gömleksiz & Bozpolat, 2013;Hazır-Bıkmaz et al, 2013;Yetkiner et al, 2019). Some factors such as quicker data collection through quantitative methods, the ability to determine the limits of variables more clearly, enabling generalizability thanks to the use of tools whose validity and reliability were already proved statistically, and the objectivity of the researcher may constitute the basis for the preference of quantitative research methods in the majority of the research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EPÖ anabilim dalı YÖK 2010 verilerine göre 52 üniversitede yer almaktadır (Erişti, 2013). Alanyazın incelendiğinde genelde eğitim bilimleri alanında (Karadağ (2009;Karadağ, 2010;Tavşancıl vd., 2010) özelde ise Eğitim Programları ve Öğretim alanında lisansüstü tezlerin incelenerek alandaki araştırma eğilimlerinin belirlenmeye çalışıldığı görülmektedir (Altın, 2004;Bıkmaz, Aksoy, Tatar ve Altınyüzük, 2013; Demirhan İşcan ve Hazır Bıkmaz, 2012;Demirel, Ayvaz ve Köksal, 2008;Gömleksiz ve Bozpolat, 2013;Özdemir ve Arı ,2008;Saracaloğlu ve Dursun, 2010;Schreglmann, 2016;Yetkiner, Acar, Erdol ve Ünlü, 2019). Özellikle bir bilim dalının en üst öğrenim düzeyini temsil eden doktora tezleri araştırmacıların başvuracağı kaynaklar arasında en önemlilerinden biri olarak görülebilir.…”
Section: Introductionunclassified